The Effects of Six Weeks of Endurance Training and CGRP Inhibition on Nrf2 and AKT Expression in the Hippocampal Tissue of Male Wistar Rats - Maryam Zare; Shila Nayebifar; Soheil Aminizadeh; Majid Vahidian-Rezazadeh (Hindawi Limited, 2022)
Purpose. To study the effects of a six-week endurance training protocol and calcitonin gene-related peptide (CGRP) inhibition on the nuclear factor erythroid 2-related factor 2 (Nrf2) and protein kinase B (PKB) or AKT expression in the hippocampal tissue of male Wistar rats. Main Methods. Building on a controlled experimental design with a posttest, 28 healthy Wistar male rats were randomly assigned to four groups (n=7 per group), including control, control+CGRP inhibition, endurance training, and endurance training+CGRP inhibition groups. The training groups were trained for six weeks. Rats in the CGRP inhibition group received CGRP receptor antagonist daily (0.25 mg/kg) via intravenous (IV) injection. The Nrf2 and AKT (PKB) expression was measured using the real-time PCR technique. Results. In the endurance training group, Nrf2 expression in the hippocampal tissue was increased significantly more than in other groups (P<0.05). There was also a significant increase in the AKT expression in the endurance training group compared to the control group (P=0.048) and in the endurance training+CGRP inhibition compared to the control group (P=0.012). In addition, there was no significant relationship between AKT (PKB) and Nrf2 (r=−0.27, n=28, P=0.16). Conclusion. Endurance training alone has been able to increase Nrf2 and AKT (PKB) mRNA levels in the hippocampal tissue, considering that endurance training had no significant effect on AKT and Nrf2 expression after adding to CGRP inhibition.